The mediterranean diet in cancer prevention: A review - Kontou, N.; Psaltopoulou, T.; Panagiotakos, D; Dimopoulos, M.A.; Linos, A. (Journal of Medicinal Food, 2011)
The Mediterranean dietary pattern has a well-established beneficial role in health promotion. Epidemiologic studies reveal the protective role of adherence to this pattern on overall cancer incidence and mortality. This review examines results from prospective cohort, cross-sectional, and case-control studies assessing the role of the Mediterranean diet in cancer prevention. Original research studies that were published in English between 1985 and April 6, 2010, were selected through a computer-assisted literature search (i.e., PubMed and Scopus). From the initial search, 273 papers were selected. After the titles and the abstracts of these papers were read for relevance to this review, 17 studies were selected and are discussed here; 8 had a prospective design, 7 were case-control, 1 was a randomized screening study, and 1 was an interventional study. Although there is a lack of definitive evidence for the association of Mediterranean diet with various types of cancer, a dietary pattern emphasizing the consumption of fruits and vegetables, whole grains, legumes, nuts, seeds, and low-fat dairy products could be highly recommended for all people, and especially those at risk for cancer. © 2011 Mary Ann Liebert, Inc.
Keywords: Cancer; Mediterranean diet; mortality